ANALISIS PEMBELAJARAN PBL PADA KEMAMPUAN BERPIKIR KRITIS DALAM PEMECAHAN MASALAH SISWA KELAS IV DI SDN SUKUN 2 MALANG - Rabita, Olivia; Siti Halimatus Sakdiyah; Prihatin Sulistyowati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The implementation of Problem-Based Learning (PBL) has been attempted in fourth-grade social studies at SDN Sukun 2 Malang as a response to global demands for critical thinking and problem-solving abilities. This research aims to comprehensively describe the PBL implementation process, analyze the development of students' critical thinking skills, and identify the supporting and hindering factors in the implementation of PBL and the development of fourth-grade students' critical thinking skills at SDN Sukun 2 Malang in solving social studies problems. This research used a qualitative approach with an analytical descriptive design, with 27 fourth-grade B students as subjects. The research instruments included observation sheets, interview guides, and documentation. Data were analyzed using the Miles and Huberman model, and data validity was checked through triangulation techniques. Research findings indicate that PBL implementation proceeded through stages of providing contextual problems, group collaboration, discussion and problem-solving, product creation (slogan), and process performance assessment, with the teacher acting as a facilitator and motivator. The application of PBL in the classroom was supported by the active role of the teacher, the availability of learning facilities, and student enthusiasm in group work. PBL in the classroom successfully encouraged students to be more active, critical thinkers, and collaborative, although it still faced challenges requiring further adaptation and habituation.